Beyond Antibiotic Therapy: Holistic Assessment and Primary Care Management of Typhoid Fever in an Elderly Patient - Arti Febriayani Hutasuhut; Chynthia Ferdinia Putri; Salwa Fadhilah; Salwa Putri Oktaviani; Sela; Sely Diki Oktiyanda; Shabina Adinia Yonny (Biomedical Research and Theory Letters, 2026)
Typhoid fever remains a significant public health challenge in developing countries, particularly in areas with inadequate sanitation, limited access to clean water, and poor food hygiene practices. Although antibiotic therapy remains the primary treatment strategy, successful management of typhoid fever also requires comprehensive evaluation of environmental, behavioral, nutritional, and social determinants that may influence disease transmission and recovery outcomes. This study aimed to describe the implementation of a holistic assessment approach in the primary care management of typhoid fever in an elderly patient at Sukarame Community Health Center, Bandar Lampung, Indonesia. A 57-year-old woman presented with a three-day history of fever accompanied by headache, nausea, fatigue, and generalized weakness. Clinical examination revealed stable hemodynamic status without severe complications. Laboratory findings demonstrated elevated Widal titers for Salmonella typhi and Salmonella paratyphi, supporting the diagnosis of typhoid fever. Holistic assessment identified several contributing risk factors, including the consumption of unhygienic food, inadequate environmental sanitation, limited awareness of food safety, and age-related vulnerability that potentially increased susceptibility to systemic infection. The patient received protocol-based pharmacological therapy consisting of thiamphenicol, paracetamol, omeprazole, B-complex vitamins, and domperidone, combined with non-pharmacological interventions including adequate rest, nutritional modification, hydration support, hygiene education, and environmental sanitation counseling. Educational interventions emphasized safe food consumption, hand hygiene, and prevention of household transmission. Following comprehensive management, the patient demonstrated significant clinical improvement with reduced fever, decreased nausea, improved physical condition, and recovery of daily functional activities. This case highlights that typhoid fever management in primary healthcare settings should extend beyond antibiotic administration alone. Integrating holistic assessment into clinical management allows healthcare providers to identify behavioral, environmental, and social determinants contributing to disease occurrence and recovery. The implementation of patient-centered and preventive approaches in primary healthcare may improve therapeutic outcomes, strengthen community awareness, and reduce the risk of recurrent enteric infections in endemic settings.